National disaster risk reduction and management plan 2011-2028. (National Disaster Risk Reduction Management Council (NDRRMC),Department of National Defense, 2011)
The National Disaster Risk Reduction and Management Plan (NDRRMP)fulfills the requirement of RA No.10121 of 2010,which provides the legal basis of policies, plans and programs to deal with disasters. The NDRRMP covers four thematic areas, namely, (1) Disaster Prevention and Mitigation; (2)Disaster Preparedness; (3)Disaster Response; and (4) Disaster Rehabilitation and Recovery,which correspond to the structure of the National Disaster Risk Reduction and Management Council (NDRRMC).